A Survey and Ranking of Common Particleboard Materials Using Grey Relational Grade (GRG) - Chukwunedum, Ogochukwu Chinedum; Nwobi-Okoye, Chidozie Chukwuemeka; Ekwueme, Godspower Onyekachukwu; Chinazom, Anizoba, Daniel (Journal of Industrial Engineering & Management Research, 2025)
In this research study fifteen (15) different composites of particleboards were studied based on their five (5) common physical and mechanical properties, and was graded and ranked based on these properties using Grey Relational Grade (GRG). Their common properties upon which the analysis was done and results were obtained are: Density (D), Water Absorption (WA), Thickness Swelling (TS), Modulus of Rupture (MOR), and Modulus of Elasticity (MOE). The Grey Relational Grade (GRG) used in this research study for the grading and ranking showed that the particleboard made from Sawdust Wastes and Plastic-Based Resin (Waste Styrofoam) has the best Grey Relational Grade with a value of 0.8143 (81.43%) GRG, and was ranked number one, depicting the particleboard composition with the best physical and mechanical properties. From the Grey Relational Grade results, Cement-Bonded particleboard made from Pine (Pinus Caribaea M.) Sawdust and Coconut Husk/Coir (Cocos Nucifera L.) showed the least GRG with a value of 0.4279 (42.79%) GRG, and was ranked the least, number fifteen, depicting the particleboard composition with the poorest physical and mechanical properties. The results from this research study will serve as a framework which will aid and guide industries in the wood and allied products (composite particleboard) manufacturing to obtain the optimized composition of composite particleboards (CPB’s) for production. This investigative research will increase the knowledge and development, as well as the best utilization and application of the investigated composite particleboard, as well as improve the economy of both the manufacturing industries and the nation en large through these allied-wood products.